2008
DOI: 10.1093/beheco/arn072
|View full text |Cite
|
Sign up to set email alerts
|

Courtship attention in sagebrush lizards varies with male identity and female reproductive state

Abstract: Previous experiments suggest that males spend more time with the more receptive of two novel females or the one with the higher fitness potential. However, males often court individual females repeatedly over a season; for example, male lizards sequentially visit familiar females as they patrol territorial boundaries. It may benefit males to vary display intensity as they move between multiple females. In this study, we explored the factors influencing amount of male courtship to familiar females in the Sagebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…In our study, we did not find evidence of any kind of behavioural adjustment for the fan display. Our finding, however, is in agreement with other studies which showed that courtship displays were more driven by internal male properties or male state and less by the external environment (Ruiz et al 2008;Lehtonen et al 2011). Limited behavioural flexibility could be driven by genes, prior experience, environmental factors and/or physiology, such as metabolism or hormones (Sih et al 2004;Sih & Bell 2008;Wolf & Weissing 2010;Garamszegi et al 2012).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, we did not find evidence of any kind of behavioural adjustment for the fan display. Our finding, however, is in agreement with other studies which showed that courtship displays were more driven by internal male properties or male state and less by the external environment (Ruiz et al 2008;Lehtonen et al 2011). Limited behavioural flexibility could be driven by genes, prior experience, environmental factors and/or physiology, such as metabolism or hormones (Sih et al 2004;Sih & Bell 2008;Wolf & Weissing 2010;Garamszegi et al 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Our finding, however, is in agreement with other studies which showed that courtship displays were more driven by internal male properties or male state and less by the external environment (Ruiz et al. ; Lehtonen et al. ).…”
Section: Discussionsupporting
confidence: 94%
“…It is likely that other factors not examined in our study (e.g., individual variation in behavior; Ruiz et al. ) also influence male total pushup time.…”
Section: Discussionmentioning
confidence: 91%
“…These results may alternatively suggest that males respond to higher value females with increased courtship (e.g., Ruiz et al. ), as pushups and shuddering together contribute to courtship behavior (Martins ). It is interesting to note, however, that female value explains only a small amount of the overall variation in male pushup time (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In most animal species, both males and females display some degree of plasticity in their reproductive behaviour in order to optimize their reproductive investment (Engqvist & Sauer, 2002). When the potential benefits of reproduction are low, individuals may invest little in current reproduction and save energy for future reproduction (Engqvist & Sauer, 2002;Kvarnemo, Forsgren, & Magnhagen, 1995;Muramatsu, 2010;Ruiz, Davis, & Martins, 2008). They thus need to assess their current competitive ability and probability of reproductive success to maximize their lifetime reproductive success.…”
Section: Introductionmentioning
confidence: 99%